Predictors of Acute Renal Failure During Extracorporeal Membrane Oxygenation in Pediatric Patients After Cardiac Surgery. Issue 5 (4th December 2015) - Lv, Lin; Long, Cun; Liu, Jinping; Hei, Feilong; Ji, Bingyang; Yu, Kun; Hu, Qiang; Hu, Jinxiao; Yuan, Yuan; Gao, Guodong
Abstract: Acute renal failure (ARF) is associated with increased mortality in pediatric extracorporeal membrane oxygenation (ECMO). The aim of this study was to identify predictors of ARF during ECMO in pediatric patients after cardiac surgery. A retrospective study analyzed 42 children (≤15 years) after cardiac surgery requiring venous‐arterial ECMO between December 2008 and December 2014 at Fuwai Hospital. ARF was defined as ≥300% rise in serum creatinine (SCr) concentration from baseline or application of dialysis. Multivariate logistic regression was performed to identify the predictors of ARF during ECMO. A total of 42 children (age, interquartile range [IQR], 13.0 [7.2–29.8] months; weight, IQR, 8.5 [6.7–11.0] kg) after cardiac surgery requiring ECMO were included in this study. The total survival rate was 52.4%, and the incidence of ARF was 40.5%. As the result of univariate analysis, ECMO duration, cardiopulmonary resuscitation, maximum free hemoglobin (FHB) during ECMO, lactate level, and mean blood pressure before initiation of ECMO were entered in multiple logistic regression analysis. In multiple logistic regression analysis, FHB during ECMO (OR 1.136, 95% CI 1.023–1.261) and lactate level before initiation of ECMO (OR 1.602, 95% CI 1.025–2.502) were risk factors for ARF during ECMO after pediatric cardiac surgery. There was a linear correlation between maximum SCr and maximum FHB (Pearson's r  = 0.535, P  = 0.001). Maximum SCr during ECMO has also a linear correlation with lactate level before initiation of ECMO (Pearson's r  = 0.342, P  = 0.044). Increased FHB during ECMO and high lactate level before initiation of ECMO were risk factors for ARF during ECMO in pediatric patients after cardiac surgery.